Employment law : a very short introduction - Cabrelli, David A. (Oxford : Oxford University Press, 2022)
In today's society, work takes up a vast proportion of the time and energy of ordinary people. Although use of the phrase 'work-life balance' is now commonplace in the media and ordinary conversation, people work longer hours than ever before. However, rather than purely a means to an end in terms of supporting oneself financially, the workplace is a place to develop skills and talents and build lasting friendships. For these reasons, people want to know about their rights in the workplace. Issues of equal pay, discrimination, discharge/dismissal, and redundancy are prevalent within the media, and there is a growing public appetite for knowledge of the law governing the employment relationship. This book provides an overview of the main kinds of employment rights and labour laws found in many countries.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 17, 2022).
Keywords: Labor laws and legislation